Hidradenitis Suppurativa Area and Severity Index Revised (HASI‐R): psychometric property assessment. (30th December 2020) - Goldfarb, N.; Lowes, M. A.; Butt, M.; King, T.; Alavi, A.; Kirby, J. S.
Summary: Background: Validated, reliable, globally accepted outcome measurement instruments for hidradenitis suppurativa (HS) are needed. Current tools to measure the physical signs domain for HS rely on lesion counts, which are time‐consuming and unreliable. Objectives: To assess the reliability and validity of the Hidradenitis suppurativa Area and Severity Index Revised (HASI‐R) tool, a novel method for assessing HS severity, incorporating signs of inflammation and body surface area involved. Methods: The measurement properties of the HASI‐R tool were evaluated. The tool was created by combining the previously published HASI and Severity and Area Score for Hidradenitis instruments. Twenty raters evaluated 15 patients with HS in a hospital‐based ambulatory dermatology clinic. The objectives of the study were to assess inter‐ and intra‐rater reliability of the HASI‐R and its components, as well as its construct and known‐groups validity. Existing lesion count‐based clinician‐reported measures of HS and their components were also assessed. Raters were also asked their preferences regarding the various HS severity assessment tools. Results: The HASI‐R had moderate inter‐rater reliability [intra‐class correlation coefficients (ICC) 0·60]. This was better than all other HS physical sign outcome measures evaluated, which had poor inter‐rater reliability (ICC < 0·5). HASI‐R had the highest intra‐rater reliability (ICC 0·91). The HASI‐R had good construct validity and demonstrated known‐groups validity. The HASI‐R was also the most preferred tool by all raters. Conclusions: Results from the clinometric assessment of the HASI‐R are encouraging, and support continued evaluation of this clinician‐reported outcome measure. Abstract : What is already known about this topic? The reliability of physician‐reported outcome measures for hidradenitis suppurativa (HS), comprised of counting lesions, has come under scrutiny. Current physician‐reported outcome measures lack assessment of body surface area (BSA). The original Hidradenitis suppurativa Area and Severity Instrument (HASI) and Severity and Area Score for Hidradenitis (SASH) are two HS severity assessment instruments combining signs of inflammation with BSA, dispensing with traditional lesion counts. What does this study add? The two groups that created the HASI and SASH merged the two instruments into a single tool called the Hidradenitis suppurativa Area and Severity Instrument Revised (HASI‐R). Clinometric assessment of the HASI‐R was completed, including inter‐ and intra‐rater reliability, convergent/divergent validity and known‐groups validity. Results from the clinometric assessment are encouraging and support continued validation of the HASI‐R. What are the clinical implications of this work? Currently, only one drug is approved by the US Food and Drug Administration for the treatment of HS. The use of outcome measures in clinical trials with lower reliability, higher limits of agreement and higher minimal detectable change increases the risk that a treatment effect will be obscured (false‐negative), which can result in the discarding of promising new therapies. High‐quality outcome measures for HS are urgently needed. Linked Comment: Emtestam et al. Br J Dermatol 2021; 184 :796–798 .